2010
DOI: 10.1111/j.1600-051x.2010.01563.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary MMP‐8, TIMP‐1, and ICTP as markers of advanced periodontitis

Abstract: Salivary MMP-8, TIMP-1, ICTP, and especially their ratios and combinations are potential candidates in the detection of advanced periodontitis. Differentiating periodontitis and control subjects with salivary MMP-8 detection is dependent on the selected techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
233
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 180 publications
(257 citation statements)
references
References 38 publications
19
233
3
2
Order By: Relevance
“…11 Although in many earlier studies saliva has been used, being easily available and a noninvasive specimen to detect the various cytokines associated with periodontal diseases, in our study, we used plasma sample because markers, such as TNF-α and IL-6 are reported to be present in less amount in saliva. [12][13][14] In this study, the proportion of male population was higher in comparison to the female population and the male population showed greater duration of uncontrolled diabetes as well.…”
Section: Discussionmentioning
confidence: 82%
“…11 Although in many earlier studies saliva has been used, being easily available and a noninvasive specimen to detect the various cytokines associated with periodontal diseases, in our study, we used plasma sample because markers, such as TNF-α and IL-6 are reported to be present in less amount in saliva. [12][13][14] In this study, the proportion of male population was higher in comparison to the female population and the male population showed greater duration of uncontrolled diabetes as well.…”
Section: Discussionmentioning
confidence: 82%
“…Passoja A et al, [21] in their study found, MMP-8 concentrations to be significantly higher in smokers as compared to nonsmokers with relation to Probing pocket depth and clinical attachment. Similarly Gursoy UK, et al, [22] found in their study that smokers with periodontitis had a higher expression of MMP-8 with increase in the probing pocket depth as compared to Non-smokers with periodontitis. A significant correlation between increased MMP-8 levels and periodontal disease severity was suggested by Liu et al, [18] who reported increased local MMP-8 expression in the periodontal tissues of smokers compared to the nonsmokers.…”
Section: (Cpn) and Group Ii-b (Hn) Group I-a (Cps) And Group Ii-a (Hmentioning
confidence: 94%
“…1,2 The levels of MMPs have been studied extensively in gingival crevicular fluid (GCF) 3,4 and saliva 5,6 and have been shown to be elevated in patients with periodontitis compared to periodontally healthy subjects. Further, periodontal treatment resulted in decreases in GCF levels of MMPs.…”
Section: Introductionmentioning
confidence: 99%